Consumo de antibióticos de reserva en el servicio de cirugía del Hospital I Luis Albrecht – EsSalud- Trujillo, febrero - diciembre del 2016 - Carranza Barreto, Karen Stephanie (2017)
The present report of pre-professional practices aims to characterize the use of reserve antibiotics in the Surgery Service of the Luis Albrecht-EsSalud-Trujillo Hospital, February - December, 2016. The surgery service has a total of 5 hospitalization beds, and the methodology used was ATC / DDD based on DDD / 100 bed-days; for the purpose of the study the database of the I Albrecht Hospital was accessed. The results obtained according to the monthly frequency of use were: ceftriaxone and imipenem + cilastatin are the most commonly used antibiotics; and ceftriaxone is the most commonly used antibiotic with 30,7%, followed by imipenem + cilastatin with 28%, ciprofloxacin with 26,5%, vancomycin with 10,5%, metronidazole with 4,24% and ceftazidime with 0,11%. According to the frequency of prescription, 26% of antibiotics are dose-dependent and 74% are time-dependent. The results according to DDD were ceftriaxone with a DDD / 100 bed-day of 23,79, ciprofloxacin with a DDD / 100 bed-day of 8.20, metronidazole with a DDD / 100 bed-day of 2,19, imipenem + cilastatin with a DDD / 100 day beds of 10,85, vancomycin with a DDD / 100 bed-day of 4,07 and ceftazidime with a DDD / 100 bed-day of 0,02. The total cost in the use of reserve antibiotics was S/. 781.2, S/. 572.39, S/. 98.56, S/. 5145.99, S/. 785.01 and S/. 4.66 for ceftriaxone, ciprofloxacin, metronidazole, imipenem, vancomycin and ceftazidime respectively; concluding that the antibiotic with the highest frequency of use and higher DDD is ceftriaxone, and the most expensive antibiotic imipenem + cilastatin